Nepal’s Water Diplomacy: Relationship with her Neighbours - Dhungel, Dwarika Nath (NCWA Annual Journal, 2023)
Water is the most important natural resource of Nepal. Its importance and demand have been increasing over time, not only in Nepal but also in all of the South Asia region. The Ganges River Basin is the most populous region in the world. People living in and around the Basin rely mainly on the Ganges River to meet their growing water requirements. However, the Ganges River is mostly fed by the rivers that originate in Nepal and Tibet Autonomous Region of China. This paper explores the possibility of Nepal using water as a driver for the development of the region as part of its regional diplomacy.